2013
DOI: 10.1590/s1981-67232013005000036
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant capacity, total phenolic content and mineral elements in the fruit peel of Myrciaria cauliflora

Abstract: The in vitro antioxidant capacity, total phenolic content and mineral elements of the fruit peel of Myrciaria cauliflora were investigated. The antioxidant capacity was analyzed by the diphenylpicrylhydrazyl (DPPH), 2,2'-azino-bis(3ethylbenzthiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP) and β-carotene methods. The assays based on the DPPH (EC 50 = 3.18 g sample/g DPPH), ABTS •+ (1017 μmol Trolox/g sample), FRAP (1676 μM Fe 2 SO 4 /g sample) and β-carotene/linoleic acid (70% of oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…Jabuticaba fruits have a wide variety of nutrients, such as carbohydrates, minerals, amino acids, lipids, and vitamins (Wu and others ). Studying this berry, Alezandro and others (), Araújo and others (), Lima and others (), and Lima and others () evaluated the chemical composition of jabuticaba from Sabará and Paulista varieties and found a high content of minerals, K, Na, Mg, Ca, Cu, Fe, and Mn, both in the whole fruits as in their parts (skin, seed, and pulp). Alezandro and others () observed that jabuticaba seeds have high concentrations of ellagitannins and proanthocyanidins, whereas skin exhibited the highest amounts of anthocyanins and quercetin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Jabuticaba fruits have a wide variety of nutrients, such as carbohydrates, minerals, amino acids, lipids, and vitamins (Wu and others ). Studying this berry, Alezandro and others (), Araújo and others (), Lima and others (), and Lima and others () evaluated the chemical composition of jabuticaba from Sabará and Paulista varieties and found a high content of minerals, K, Na, Mg, Ca, Cu, Fe, and Mn, both in the whole fruits as in their parts (skin, seed, and pulp). Alezandro and others () observed that jabuticaba seeds have high concentrations of ellagitannins and proanthocyanidins, whereas skin exhibited the highest amounts of anthocyanins and quercetin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Here we showed that the water extract of jaboticaba seeds possesses appreciable antioxidant activity as well. Jaboticaba is promising not only as a source of antioxidants but also as a chemopreventative agent BAGATTOLI; CIPRIANI; MARIANO; CORREA; WAGNER; NOLDIN; CECHINEL FILHO; NIERO, 2016 We investigated the antinoceptive genotoxic and gastroprotector potential of metanol extract of different fruits found in Brazil Plinia glomerata and G. achachairu inhibited the growth of B16F10 tumor cells and these fruits showed promising results that could be passed on, in order to guide people who use these plants for this purpose PLAZA; BATISTA; CAZARIN; SANDAHL; TURNER; ÖSTMAN; MARÓSTICA JR, 2016 In the present study, the polyphenols profile and their contribution to the antioxidant capacity of the jaboticaba peel were analyzed using highperformance liquid chromatography (HPLC) with photodiode array (DAD), electrochemical (ECD), charged aerosol (CAD), and mass spectrometry (MS) detections…”
Section: Wu; Long; Kennelly 2013mentioning
confidence: 99%
“…Subsequentemente, as amostras foram filtradas em filtro Whatman n° 1 e os permeados utilizados para análise. O conteúdo de compostos fenólicos totais foi determinado espectrofotometricamente (HACH, modelo DR2800) pelo método de Folin-Denis como descrito por Swaine Hillis (1959), com algumas modificações (ARAÚJO et al, 2013). Em tubos de ensaio contendo 7,5 mL de água destilada foram adicionados 1000 µL dos extratos previamente diluídos, 500 µL do reagente Folin-Denis e 1000 µL de solução de carbonato de sódio 7% (p/v).…”
Section: Determinação Dos Compostos Fenólicos Totaisunclassified